THE SIGNIFICANCE OF THE CRIMEAN BRIDGE FOR RUSSIA: A POWER TOOL WITH STRATEGIC, LEGAL, AND SYMBOLIC VALUE - Emmerich, Jan (Monterey, CA; Naval Postgraduate School, 2020)
Many observers have concentrated on the territorial consequences of Crimea’s annexation in 2014. The Kerch Strait incident in November 2018 made salient the existence of a maritime dimension to this conflict. In addition, it brought into focus the longest bridge in Europe, linking Crimea to the Russian mainland. This thesis analyzes the benefit of the Crimean Bridge for Russia in three domains. First, the bridge permits Russia to further secure its strategic hold on Crimea and to exert continuous economic and political pressure on Ukraine. Second, the Crimean Bridge illustrates how Russia conceives of international law and international treaties. Furthermore, it supports Russia’s onslaught on Ukraine’s maritime integrity. Third, this imposing structure symbolizes the resurrection of Russian greatness, and at the same time, it is a monument for the man who made that possible, Vladimir Putin. As this research shows, the laissez-faire response of the international community has allowed Russia to regain strength militarily and politically, and as a nation per se, even beyond the wider Black Sea area. The international community must be wary of Russia—or any other nation—that begins to build infrastructure to assert its geostrategic interests. Approved for public release. distribution is unlimited Commander, German Navy